Identification of Oxide Compound in Dolomite Mineral from Aceh Tamiang Region - Nirmala Sari; Zulkarnain Jalil; Adi Rahwanto (Journal of Aceh Physics Society, 2013)
Indonesia has abundant mineral especially carbonate-based mineral, ike dolomite. Particularly in Aceh province's, the largest dolomite deposits is available in Aceh Tamiang district around 1.9 billion tons. Unfortunately, current use of dolomite in the industry and other applications is still limited. In this work we report the advanced preparation of dolomite using calcinations method. Whereas, with this method, the dolomite mineral can be processed into calcium and magnesium oxide which has a very wide field of application and higher values. To obtain optimal results, we also identify the effect of temperature on the formation of oxide compounds. Preliminary study using XRF founded that dolomite in village Selamat is known as the highest concentration of CaO (61.20%) followed by MgO (25.28%). It is also showed that the main phase obtained by XRD is dolomite (CaMg(CO3)2). Furthermore, after the calcinations process at 700 °C, it was founded that the formation of dolomite were CaCO3 and MgO, whereas at temperatures of 900 °C mostly the CaCO3 has decomposed into CaO. SEM observations showed that dolomite has the composition of particles distributed homogeneously along the particle agglomerate when it calcinations.